A Maternal-Effect Toxin Affects Epithelial Differentiation and Tissue Mechanics in Caenorhabditis elegans - Lehmann, Christina; Pohl, Christian (Frontiers in Cell and Developmental Biology, 2021)
Selfish genetic elements that act as post segregation distorters cause lethality in non-carrier individuals after fertilization. Two post segregation distorters have been previously identified in C. elegans, the peel-1/zeel-1 and the sup-35/pha-1 elements. These elements seem to act as modification-rescue systems, also called toxin/antidote pairs. Here we show that the maternal-effect toxin/zygotic antidote pair sup-35/pha-1 is required for proper expression of apical junction components in epithelia and that sup-35 toxicity increases when pathways that establish and maintain basal epithelial characteristics, die-1, elt-1, lin-26, and vab-10, are compromised. We demonstrate that pha-1(e2123) embryos, which lack the antidote, are defective in epidermal morphogenesis and frequently fail to elongate. Moreover, seam cells are frequently misshaped and mispositioned and cell bond tension is reduced in pha-1(e2123) embryos, suggesting altered tissue material properties in the epidermis. Several aspects of this phenotype can also be induced in wild type embryos by exerting mechanical stress through uniaxial loading. Seam cell shape, tissue mechanics, and elongation can be restored in pha-1(e2123) embryos if expression of the apical junction molecule DLG-1/Discs large is reduced. Thus, our experiments suggest that maternal-effect toxicity disrupts proper development of the epidermis which involves distinct transcriptional regulators and apical junction components.